Cash inflow and trading horizon in asset markets - Michael Razen; Jürgen Huber; Michael Kirchler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
It is conjectured that one of the major ingredients of historic financial bubbles was the inflow of money in various forms. We run 36 laboratory asset markets and investigate the joint effect of cash inflow and trading horizon on price efficiency. We show that only markets with cash inflow and long trading horizon exhibit bubbles and crashes. We also observe that markets with extended trading horizon but without cash inflow and markets with shorter trading horizon do not trigger bubbles. Finally, we report that beliefs about prices and, importantly, about (constant) fundamentals follow bubble patterns as well.
Keywords: C92; D84; G10; 330; experimental finance; cash inflow; trading horizon; backward induction; asset market; price efficiency